Analysis of Online News Media Sentiment Toward the Free Nutrisious Meals Program Policy - Abdan Syakuro; Arif Zainudin; Akhmad Habibullah (ARISTO, 2026)
With a focus on three significant media outlets Kompas.com, CNN Indonesia, and TVOne this study attempts to examine media sentiment regarding the Free Nutritious Meals Program (MBG) in Indonesia. Positive, negative, neutral, and mixed sentiment were the four categories into which sentiment was divided using a descriptive qualitative technique with content analysis. The findings indicate that neutral emotion predominates in all three media outlets' news coverage, with more descriptive and educational articles about the program's execution. However, negative sentiment also emerges, particularly in relation to issues of food poisoning and distribution constraints. On the other hand, although it is less common, positive attitude emphasizes the program's success and support. Both praise and criticism of this policy are reflected in the mixed sentiment. These results demonstrate that the media not only contributes to the dissemination of accurate information but also influences public opinion by drawing attention to certain problems. The usefulness of Agenda Setting theory in comprehending how the media decides which issues the public should find essential is also demonstrated by this study. This study's modest sample size just 15 articles from each media source and only three online news media sites were examined may not accurately represent the whole range of MBG coverage in Indonesian media. In order to map the dynamics of sentiment changes towards MBG over time, more study is advised to increase the sample size by incorporating more news sources from other platforms, including social media, and extending the data collection period. Keywords: News Media; Sentiment; Mbg Program;